Monocular diplopia‐associated migraine‐like headache induced by nicotine withdrawal. Issue 5 (17th March 2017) - He, Xiaoping; Munaf, Alvina; Idrisov, Evgeny; Everett, George; Saikaly, Sami K.; Kim, Esther; Abusaada, Khalid; Hsu, Vincent
Key Clinical Message: We describe an extremely rare case of migraine‐associated monocular diplopia developed in a 23‐year‐old man after sudden cessation of smoking. The physical examination and brain MRI scan were unremarkable. The symptoms resolved after starting nicotine patch. We reviewed the literature and discussed the diagnosis and possible mechanism of this phenomenon. Abstract : We describe an extremely rare case of migraine‐associated monocular diplopia developed in a 23‐year‐old man after sudden cessation of smoking. The physical examination and brain MRI scan were unremarkable. The symptoms resolved after starting nicotine patch. We reviewed the literature and discussed the diagnosis and possible mechanism of this phenomenon.